Re-using the gods: a 6th-c. statuary display at Sagalassos and a re-evaluation of pagan mythological statuary in Early Byzantine civic space - Jacobs, I; Stirling, L (Cambridge University Press, 2017)
In 2009, a set of under-lifesized statues was discovered on top of the pavement of the main N–S colonnaded street of Sagalassos. Their particular find contexts suggest that they had been on display along the street on top of statue brackets in its final phase. These statuettes not only survived in the cityscape into the 7th c. A.D., they were part of a large-scale renovation of the lower town datable to the second quarter of the 6th c. This exceptionally late example of displayed pagan mythological statuary provides information on what pieces of statuary were still available and considered suitable for re-use in the Early Byzantine period. In addition, the collection's composition can inform us about the preferred appearance of a bustling urban thoroughfare and something of the values and beliefs of the population at that period, since “whereas the common folk […] did not read Homer and Pindar, everyone — the butcher, the candlemaker, and the lower-class saint — could and did look at these statues”.